Migrasi Database, MySQL, Postgre Migrasi Database Mysql Ke Postgresql Pada Aplikasi Sistem Evaluasi Dosen Oleh Mahasiswa (EDOM) Jurusan Ekonomi Dan Bisnis - Muhammad Irfan Lutfi; Asrowardi, Imam; Supriyatna, Agiska Ria (Program Studi Teknologi Rekayasa Internet, Politeknik Negeri Lampung, 2023)
Implementation of Filling Out Lecturer Evaluations by Students (EDOM) which is carried out at the end of each semester during the Semester Final Examination (UAS) activities, has been developed into an online computerized information system using a MySQL database. As the amount of data in the EDOM information system increases, data storage that has a high complexity is needed, so that from the database side it must have high performance and can handle large amounts of data. For the needs of the EDOM information system, MySQL is no longer able to provide its best performance in handling large amounts of data, so a database that has better performance is needed. The purpose of this final project is to Migrate MySQL Database to PostgreSQL on Application System (Evaluation of Lecturers by Students) EDOM Department of Economics and Business, in order to overcome the problem of MySQL database which is no longer able to provide its best performance in handling large amounts of data. The system development method used is the SDLC method. Based on the results of tests carried out by testing query performance on both dbms, PostgreSQL has a stable performance compared to MySQL, at the same amount of data MySQL excels in regular updates and selects without additional clauses. Meanwhile PostgreSQL excels at creating, deleting data and complex join clauses. The next test is carried out on the application using the php function, namely microtime by writing a script at the beginning of the body and before closing the body of the html page on applications that use MySQL and PostgreSQL dbms, carried out to test the speed in loading data in EDOM system applications, the result is that the use of PostgreSQL dbms is faster in load data, because the data is presented using complex join clauses. This is because PostgreSQL supports locking at a lower level, namely row so that it becomes one of the advantages in doing database migration because the business processes in the EDOM System Application are made more effective.